Identifying Coping Strategies in Adolescents at Dharma Social Institution for Child Protection in Samarinda - Zahara, Diva Oktaviani (ITKES Wiyata Husada Samarinda, 2023)
Coping strategy is the ability to manage stress. In adolescence, stress is usually unresolved, since adolescence is a stage of adjustment and change, including both emotional and physical changes. Adolescents living in social institutions have different living environment from adolescents in general. They need to have high resilience in their lives because they experience separation from their parents, which will also negatively impact their development. This can be a factor in determining a strategy to cope with stress every day. This research aims to investigate the coping strategies used by the adolescents at Dharma Social Institution for Child Protection in Samarinda. This research is quantitative descriptive research. The data were primary data collected using coping strategy questionnaire measured by Coping Scale. The respondents of this research were adolescents who lived in Dharma Social Institution for Child Protection in Samarinda who fulfilled the inclusion and exclusion criteria. 29 respondents were selected for this research. The results of this research showed that the coping strategy used by the adolescents in the institution were problem-focused coping (51.7%) and emotion focused coping (48.3%). Based on the results of this research, it can be concluded that the majority of the adolescents use problemfocused coping strategy.